Analysis of Electrical System Reliability for Premium Customer after Installation of Automatic Change Over Switch (ACOS) - A Case Study - Arlenny, Arlenny; Pratiwi, Dessy; Situmeang, Usaha (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2025)
PLN is the electricity company that distributes electricity to customers, always tries to improve the quality of system reliability. So, it can continue to distribute electrical energy to customers and reduce the decline in Energy Not Supplied (ENS) on the PLN side. One way for PLN to avoid blackouts to the customers, especially premium customers, from planned or unplanned blackouts by installing an Automatic Change Over Switch (ACOS) on the incoming customer side. This paper aims to analysis of electrical system reliability for premium customers after Installation of Automatic Change Over Switch (ACOS). Data collection was carried out on the premium customer of 328 electricity distribution system supplied by the Senangin Feeder or Abadi Feeder from GI Garuda Sakti, Pekanbaru with a power transformer capacity at TD#4 of 60 MVA with a feeder length of 10.25 KMs using medium voltage cable channels, with a radial system. From the results of calculations carried out on the Senangin feeder, which supplies electrical energy to customers, the SAIFI (System Average Interruption Frequency Index) index value was 71,647 outages/year in 2018 and SAIDI (System Average Interruption Duration Index) was 3.44 hours/year in 2018, while the Energy Not Supplied (ENS) value in 2018 was 33,781.83 kWh and 5,124.36 kWh in 2019.